2019
DOI: 10.1248/cpb.c19-00166
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Flavone <i>C</i>-Glycosides from Oolong Tea Leaves: Chafuroside A Dihydrate and Chafuroside B Monohydrate

Abstract: Chafuroside A and chafuroside B are flavone C-glycosides isolated from oolong tea leaves. They have a number of beneficial pharmacological activities related to antiinflammation at various concentrations. However, no crystallographic study of chafurosides has yet been reported. In the present study, the crystal structures of chafuroside A and chafuroside B were investigated using single-crystal X-ray diffraction. The asymmetric unit of the chafuroside A crystal consists of one chafuroside A and two water molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…They concluded that the transformation into nanocrystals improves the bioavailability and solubility of quercetin in water, in addition to reducing OVA-induced Th2 cytokines IL-4 and IL-5 levels, and IgE production, as well as attenuating the activation of mast cells, and improving the control for allergic asthma [ 149 ]. The flavone chafuroside A (C 21 H 18 O 9 ; Figure 3 ) is a flavone C-glycosides first isolated from oolong tea leaves, which possesses an unusual structural characteristic in the ether connection of C2″-hydroxyl group of the mannose and the aglycone compounds [ 150 ]. Structure–activity studies demonstrated that the flavone moiety of chafuroside A is curved, which may positively interfere in its pharmacological activities [ 150 ].…”
Section: Controlled Flavonoid Release Systems In Asthma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the transformation into nanocrystals improves the bioavailability and solubility of quercetin in water, in addition to reducing OVA-induced Th2 cytokines IL-4 and IL-5 levels, and IgE production, as well as attenuating the activation of mast cells, and improving the control for allergic asthma [ 149 ]. The flavone chafuroside A (C 21 H 18 O 9 ; Figure 3 ) is a flavone C-glycosides first isolated from oolong tea leaves, which possesses an unusual structural characteristic in the ether connection of C2″-hydroxyl group of the mannose and the aglycone compounds [ 150 ]. Structure–activity studies demonstrated that the flavone moiety of chafuroside A is curved, which may positively interfere in its pharmacological activities [ 150 ].…”
Section: Controlled Flavonoid Release Systems In Asthma Treatmentmentioning
confidence: 99%
“…The flavone chafuroside A (C 21 H 18 O 9 ; Figure 3 ) is a flavone C-glycosides first isolated from oolong tea leaves, which possesses an unusual structural characteristic in the ether connection of C2″-hydroxyl group of the mannose and the aglycone compounds [ 150 ]. Structure–activity studies demonstrated that the flavone moiety of chafuroside A is curved, which may positively interfere in its pharmacological activities [ 150 ]. Chafuroside A was reported to be safe in mice models of colon cancer from 20 to 25 parts per million (p.p.m.)…”
Section: Controlled Flavonoid Release Systems In Asthma Treatmentmentioning
confidence: 99%